Motion Estimation of Non-Cooperative Space Objects Based on Monocular Sequence Images - Runran Deng; Dayi Wang; Wei E; Dongming Ge; Weihong Zhu (Applied Sciences, 2022)
The motion estimation of non-cooperative space objects is an important prerequisite for successfully completing on-orbit servicing, debris removing and asteroid exploration missions. The motion estimation of non-cooperative space objects is a challenging task because of the lack of prior information about the object in unknown scenarios. In this paper, a motion estimation method of non-cooperative space objects for autonomous navigation based on a monocular sequence of images is proposed. The rotational attitude estimation of the non-cooperative space object is realized by matching the feature points of adjacent frame images, and the conditions required for translational estimation are discussed. This method has small calculation costs and runs stably, which meets the requirements of real-time computation on-board. As a result, this method implements the estimation of the complete unknown information of the object, including the attitude quaternion and angular velocity. Numerical simulations and results verify the effectiveness of the proposed method.